Democratic Governance in Nigeria: The Question of Sustainability of the Fourth Republic - Victoria Jatau; Nur Koprulu (International Journal of Advanced Science and Technology, 2020)
It’s been 20 years now when Nigeria broke the backbone of military rule and transited to that of democracy. However, it remains unclear if the system can be sustained. The twenty years of unbroken democratic practice in Nigeria is at least expected to have provided the needed drive and hope to locate the country on the trajectory of sustainable democracy, but the many pitfalls present, revealed that there is still much to be done for Nigerian democracy to be set on the actual path of sustainability in terms of democratic practice. We highlighted these pathologies that befall the Nigerian democracy in its efforts towards sustainability. Using Easton’s system, we argued among other elements that sincere political elites with national interest, independent and impartial judiciary, professional bureaucracy, robust civil society, and unfettered media, all working in synergy, is required among other things to sustain Nigeria’s Democracy. There must also be equilibrium between the inputs and the outputs in the political setting. The interaction among the different elements with relatively good degree of institutionalization is hope to promote democracy in the country, enhance its sustainability and ultimately, its consolidation.